Study of the corrosion of materials in the atmosphere of Lima - Alcan method - Dionicio Padilla, Eusebio (1999)
The present study of the corrosion of materials in the atmosphere of Lima is based on the wire-screw method, carried out on the Electro Lima line (posts) that covers 60 km from coastal Lima and 43.5 km inland. The results found of the marine corrosion index with respect to the distance from the ocean using the model: X1 / 3 + Y1 / 2 = 5, where: X = distance from the ocean in Km. Y = marine corrosion index.